2013
DOI: 10.1155/2013/603713
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Burnout in Danish GPs and Exploration of Factors Associated with Development of Burnout: A Two-Wave Panel Study

Abstract: Background. We assessed risk of burnout in GPs during a 7-year followup and examined whether (1) thoughts about changing medical specialty increased the risk of burnout and (2) burned out GPs had higher job turnover rates than burnout-free GPs. Methods. In 2004 and 2012, all GPs in the county of Aarhus, Denmark, were invited to participate in a survey. Retirement status of physicians who participated in 2004 was obtained through the Registry of Health Providers in 2012. Results. 216 GPs completed both surveys.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 20 publications
5
19
0
Order By: Relevance
“…We found that GPs who were emotionally exhausted were older and more experienced than their non-exhausted colleagues, but they showed no differences with respect to gender, marital status, specialization, or work position. In line with our results, emotional exhaustion among GPs in the other studies is independent of gender [ 10 , 25 ]. However, that older and more experienced GPs are more often emotionally exhausted is different from what is suggested in other literature.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that GPs who were emotionally exhausted were older and more experienced than their non-exhausted colleagues, but they showed no differences with respect to gender, marital status, specialization, or work position. In line with our results, emotional exhaustion among GPs in the other studies is independent of gender [ 10 , 25 ]. However, that older and more experienced GPs are more often emotionally exhausted is different from what is suggested in other literature.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the prevalence of GPs’ emotional exhaustion was 18%. Similar figures have been reported among Swiss primary care doctors (19%) [ 22 ], among French and Australian trainees in general practice (16%) [ 26 , 32 ], and among Danish GPs (14%) [ 25 ]. In a study from the UK, 46% [ 33 ] and, in another study from Serbia, 58% [ 19 ] of GPs experienced high emotional exhaustion.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…40 Online supplementary table 2 shows the country-wise prevalence of burnout, EE, DP, and low PA in different studies. 9–30 In a tertiary children’s hospital, with a 22-bed pediatric intensive care unit (PICU)/neonatal Intensive care unit (ICU), a 17-bed cardiac ICU and a teaching hospital with 3-adult ICUs, Colville et al 41 found that the prevalence of burnout was 37% whereas the prevalence of clinically significant post-traumatic stress symptoms was 13%. The authors noted a degree of overlap between burnout and other measures of distress, most notably for anxiety (OR, 10.56).…”
Section: Discussionmentioning
confidence: 99%
“…While the overall prevalence of burnout was estimated to range from 2.6% to 69.9%, emotional exhaustion (EE) was observed in 8.7–63.2%, depersonalisation (DP) in 8.5–52% and low personal accomplishment (PA) in 4.4–73.3%. 8–34 Burnout prevalence varies among different subgroups of physicians (eg, general practitioners, anaesthetists, senior doctors and dentists).…”
Section: Introductionmentioning
confidence: 99%